An Ambition to Redeem His Guilts of Amir in Khalid Hosseini’s “The Kite Runner” - Ahmat Jaelani (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study not only investigates the concept of ambition in literature but also underscores its transformative impact on human existence. By adopting a descriptive qualitative approach and drawing data from the characters' dialogues in "The Kite Runner," the research unveils the nuanced dynamics of ambition and guilt redemption. Amir, a central character in the novel, emerges as a dynamic individual, navigating through a complex terrain of personal growth and evolving aspirations. His struggles and shifts in personality are intricately woven into the narrative, highlighting the profound influence of ambition on the human psyche. Furthermore, the study sheds light on the intricate interplay between Amir's sense of guilt and his subsequent ambitions. It becomes evident that his guilt serves as a catalyst for a series of ambitious pursuits aimed at redemption. This intricate web of emotions and aspirations not only propels the narrative forward but also unveils the profound ways in which literature can mirror and dissect the human experience. The findings contribute to a deeper understanding of the intricate relationship between ambition and the moral dimensions of human existence, offering insights into the transformative power of aspirations in navigating the complexities of guilt and redemption in literary contexts.